Extensão Rural em terras indígenas no estado de São Paulo: agrofloresta e turismo em aldeias Guarani - Santos, Tatiane Ribeiro dos (Universidade Federal de São Carlos, 2019)
Regarding ethnodevelopment initiatives with traditional communities, indigenous peoples occupy a recognized space within public policies. In the context of family farming, in which indigenous people are beneficiaries by law, a set of rural extension actions is developed in the State of São Paulo based on the State Program for Sustainable Rural Development (PDRS): Microbasins II, Market Access, which contemplates the "Strategy of Participation of Indigenous Populations." In this context, the objective of the research was to evaluate the conceptions, ways of implementation, the perceptions and social, cultural and environmental impacts of the activities of this program in Aldeia Boa Vista and Aldeia Itaoca Tupi, where agroforestry and rural tourism systems were implemented, respectively.The methodological orientations involved bibliographic and documentary survey and case study.It was noted that the changes of government directly affect the actions of public rural extension mainly impacting family farming. Indigenous peoples are even more disadvantaged because they do not have However, agroecology as well as the education and formation of socio-technical networks have proved to be positive instruments to overcome the challenges related to interculturalism faced by extensionists in the field. Bureaucratic obstacles were the biggest difficulties for the implementation of the Program. However, the final assessment is positive: there have been advances in ATER services provided to indigenous communities in the state of São Paulo and the initiatives have created references that can guide the creation and / or improvement of policies aimed at strengthening and emancipating indigenous people in the environment rural.

Con respecto a las iniciativas de desarrollo étnico con las comunidades tradicionales, los pueblos indígenas ocupan un espacio reconocido dentro de las políticas públicas. En el contexto de la agricultura familiar, en la cual los pueblos indígenas son beneficiarios por ley, se desarrolla un conjunto de acciones de extensión rural en el Estado de São Paulo, basado en el Programa Estatal para el Desarrollo Rural Sostenible (PDRS): Microbasins II, Market Access que "Estrategia de participación de las poblaciones indígenas". En este contexto, el objetivo de la investigación fue evaluar las concepciones, formas de implementación, las percepciones y los impactos sociales, culturales y ambientales de las actividades de este programa en Aldeia Boa Vista y Aldeia Itaoca Tupi, donde se implementaron los sistemas de agrosilvicultura y turismo rural, respectivamente. Las orientaciones metodológicas incluyeron encuestas bibliográficas y documentales y estudios de casos. Se observó que los cambios de gobierno afectan directamente las acciones de extensión rural pública que afectan principalmente a la agricultura familiar. están aún más en desventaja porque pueden no tener Sin embargo, la agroecología, así como la educación y la formación de redes sociotécnicas, han demostrado ser herramientas positivas para superar los desafíos relacionados con la interculturalidad que enfrentan los extensionistas en el campo. Los obstáculos burocráticos fueron las mayores dificultades para la implementación del Programa. Sin embargo, la evaluación final es positiva: ha habido avances en los servicios de ATER prestados a las comunidades indígenas en el estado de São Paulo y las iniciativas han creado referencias que pueden guiar la creación y / o mejora de políticas destinadas a fortalecer y emancipar a los pueblos indígenas en el medio ambiente. rural
Rural Extension in indigenous lands in São Paulo state: agroforestry and tourism in Guarani villages
Extensión rural en tierras indígenas en el estado de São Paulo: agroforestería y turismo en pueblos Guarani
Keywords: Terras indígenas; Sistemas agroflorestais; Turismo; Indigenous lands; Agroforestry systems; Tourism; Tierras indígenas; Sistemas agroforestales; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL; CIENCIAS SOCIAIS APLICADAS::TURISMO